The Similarities Between Shukur Kholmirzayev's Story "Kulaqcho`Zma" and Otkir Hashimov's Story "Chana" Are About the Story of the Townspeople - Yakubjanov Nuriddin Ravshanovich (Open Academia, 2023)
This article provides information about the characteristics of Shukur Kholmirzayev's stories and the similarities between his story "Kulaqcho`zma" and the characters of O'tkir Hashimov's story "Chana".